PRIVED: a Privacy Model for Heterogeneous Mobile Networks - Matos, Alfredo (2013)
We propose a network-oriented privacy model (PRIVED) composed by a well deﬁned information model, using events, information sets and relationships to deﬁne the conceptual privacy relationships that can occur in the network. We propose formal rules and a network instantiation, using linkability and correlation as the main tools for network applicability. We also use the model to determine the best approaches towards privacy protection in the network, resulting in a vertical/horizontal network privacy dichotomy.